Can’t See the Wood For the Logframe: Integrating Logframes and Theories of Change in Development Evaluation - and Freer, Gordon; Lemire, Sebastian (Canadian Journal of Program Evaluation, 2019)
There are numerous ways in which to model the underlying theory of programs. In the context of international development evaluation, the most ubiquitous are likely “logframes” and to some extent “theories of change,” both of which may serve to guide program development and management, monitoring, and evaluation. While logframes and theories of change are often developed in parallel, they are rarely fully integrated in their practical application. Drawing on lessons from a recent theory-based evaluation, this article argues that fully integrating the program theory of change within the program logframe provides for a stronger and more holistic understanding of program progress.